2017
DOI: 10.5860/crl.78.2.16580
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Use of Author Identifiers and Researcher Networking Tools

Abstract: This cross-sectional survey focused on faculty use and knowledge of author identifiers and researcher networking systems, and professional use of social media, at a large state university. Results from 296 completed faculty surveys representing all disciplines (9.3% response rate) show low levels of awareness and variable resource preferences. The most utilized author identifier was ORCID while ResearchGate, LinkedIn, and Google Scholar were the top profiling systems. Faculty also reported some professional us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
(6 reference statements)
1
14
0
Order By: Relevance
“…Nature found that just under half of the more than 3,500 scientists and engineers they surveyed visit ResearchGate regularly (Van Noorden, 2014), while a recent survey of over 20,000 respondents by researchers at Utrecht University Library found that 61% who have published at least one paper use ResearchGate Matthews, 2016). Other measures of the proportion of researchers using ResearchGate range from 15% to 65% depending on the population studied (Campos & Valencia, 2015;Haustein et al, 2014;Laakso et al, 2017;Lupton, 2014;Madhusudhan, 2012;Mahajan, Singh, & Kumar, 2013;Meishar-Tal & Pieterse, 2017;Míguez-González, Puentes-Rivera, & Dafonte-Gómez, 2017;Mikki et al, 2015;Ortega, 2015;Singh, 2016;Tran & Lyon, 2017).…”
Section: Researchgatementioning
confidence: 99%
See 3 more Smart Citations
“…Nature found that just under half of the more than 3,500 scientists and engineers they surveyed visit ResearchGate regularly (Van Noorden, 2014), while a recent survey of over 20,000 respondents by researchers at Utrecht University Library found that 61% who have published at least one paper use ResearchGate Matthews, 2016). Other measures of the proportion of researchers using ResearchGate range from 15% to 65% depending on the population studied (Campos & Valencia, 2015;Haustein et al, 2014;Laakso et al, 2017;Lupton, 2014;Madhusudhan, 2012;Mahajan, Singh, & Kumar, 2013;Meishar-Tal & Pieterse, 2017;Míguez-González, Puentes-Rivera, & Dafonte-Gómez, 2017;Mikki et al, 2015;Ortega, 2015;Singh, 2016;Tran & Lyon, 2017).…”
Section: Researchgatementioning
confidence: 99%
“…edu, which is preferred by researchers in the social sciences and especially the humanities Campos-Freire & Rúas-Araújo, 2016;Elsayed, 2015;Jamali et al, 2016;Matthews, 2016;Mikki et al, 2015;Nández & Borrego, 2013;Ortega, 2015;Thelwall & Kousha, 2015;Thelwall & Kousha, 2017;Van Noorden, 2014). Despite these disciplinary differences, however, ResearchGate is more heavily used by researchers overall than Academia.edu Campos-Freire & Rúas-Araújo, 2016;Elsayed, 2015;Jamali et al, 2016;Laakso et al, 2017;Matthews, 2016;Meishar-Tal & Pieterse, 2017;Míguez-González et al, 2017;Mikki et al, 2015;Ortega, 2015;Singh, 2016;Tran & Lyon, 2017;Van Noorden, 2014). Use of ResearchGate is notably higher than that of Academia.edu among senior researchers Matthews, 2016;Mikki et al, 2015).…”
Section: Researchgatementioning
confidence: 99%
See 2 more Smart Citations
“…This would better reflect their true output than ASNs currently do, and reliability might be further improved by dedicating a staff position to monitoring the accuracy and validity of profiles on academic social networks. Tran and Lyon (2017) found that there was much confusion among faculty about the multiple profile systems that exist (both external and internal), and felt there was a role for the library in educating faculty about them, which is one possible resolution. At this point there are more questions than answers, and few solutions-but they are questions that we must begin to ask, and attempt to answer.…”
Section: Discussionmentioning
confidence: 99%